The Escape is The Message: Andrea Maturana and The Impossible Quotes of a Writing in Transition (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
The writing of Andrea Maturana (Chile, 1969) can be read as an aesthetic and narrative incursion or the nebulous historical and political anxieties of the youth segment of a society, the Chilean one, which at the beginning of the nineties sought to leave behind a political authoritarian order. Then, the stories of these young writers outlined an imaginary characterized by the instability of a world vitally defined by its fractures, its conflicts, and the complex interaction between its members. In the urban scenes of coexistence, encounters, friction, and mutual damage narrated by Maturana, the transience of everyday life created figures through experiences conceived or defined by traumatic gestures. Faced with these figures, their tensions, and the places where they interacted, his writing mapped a web of emotions in narrative spaces obsessed with the regulation of all closeness with others.